The voyage out - Woolf, Virginia, 1882-1941. (New York : Barnes & Noble Classics, 2004)
We meet young free-spirited Rachel Vinrace aboard her father's ship, the Euphrosyne, departing London for South America. Surrounded by a clutch of genteel companions -- among them her aunt Helen, who judges Rachel to be "vacillating," "emotional," and "more than normally incompetent for her years" -- Rachel displays a startling maturity when she finds her engagement to the writer Terence Hewet listing toward disaster.
Originally published: London : 1915.
Keywords: Young women -- Travel -- South America -- Fiction; British -- Travel -- South America -- Fiction; Man-woman relationships -- Fiction; Ocean travel -- Fiction